Identification and characterization of class 1 integron among multidrug-resistant and Environmental Escherichia coli in Diyala - Al-Obeidi, Dina N.A.; Al-Taai, Hadi R. Rasheed; Mubarak, Kareem Ibrahim (Journal of Neonatal Surgery, 2025)
This study examines the incidence and characteristics of the Class 1 integrons in the Escherichia coli isolates coming from clinical and environmental sources. 15 isolates were tested; thirteen (86.6%) of the 15 isolates tested positive for class 1 integron, whereas none of the other isolates, irrespective of class, had any introns found. The incidence of HS549/HS550 genes associated with 3’CS Clinical Integron among local Escherichia coli. Fifteen E. coli samples were screened for 3’CS Clinical Integron, a clinical class 1 intgrons marker. Eleven of the fifteen samples (73.3%) were positive with variable ranges and frequencies of MRG284/MRG285 genes associated with the environmental cassette among local E. coli. Fifteen E. coli samples were screened for the environmental cassette, a marker for environmental class 1 integrin. Ten out of fifteen clinical samples (66.6%) were integrons. After screening six of the isolates, the gene cassettes for class 1 integrons were detected in the six isolates, which include those encoding resistance to trimethoprim dfrA5, aminoglycosides aadA1, sulfonamides (sul1), mercury reductase (mer operon), and those encoding a novel transporter and a short chain (dehydrogenase/reductase) in the selected isolates, which confer resistance to trimethoprim/sulfamethoxazole and aminoglycosides, respectively. Fifteen different patterns or arrangements of the gene cassettes were found. Our results indicate that class 1 integrons are widely distributed among MDR-UPEC strains in Diyala, which may directly or indirectly contribute to the selection of MDR strains. These findings are important for better understanding the factors and mechanisms that promote multidrug resistance among UPEC strains. Also, more research is needed to understand the transfer of integrons from clinical to environmental bacteria. This study offers significant insights into disseminating integron-mediated resistance, emphasizing the critical role of integrons as a focal point in public health initiatives aimed at combating antibiotic resistance